2016
DOI: 10.5455/njppp.2016.6.23022016131
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of aquaporins expressions and its impact on alleviating diabetic complications in rats: role of Citrullus colocynthis

Abstract: Background: Aquaporins (AQPs) belong to a class of small, integral membrane proteins that enable water transfer across the plasma membranes of cells as a reaction to osmotic gradients. There are 13 known types of AQPs in humans (AQP0 to AQP12), which are expressed in various organs such as the kidney, brain, liver, lungs, and salivary glands. In patient with diabetes mellitus, a reduction in salivary secretion is noted in concurrence with low salivary AQP5 levels. The Citrullus colocynthis (CC) extracts were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…These findings align with an earlier investigation (Ismail et al, 2016) which found that diabetes significantly downregulated AQP1 expressions in renal tissues compared with control. Another study also (Nielsen et al, 2002) suggested that the lower aquaporins levels in renal tubules could influence nephron water management and represent the development of acute kidney injury.…”
Section: /16supporting
confidence: 92%
“…These findings align with an earlier investigation (Ismail et al, 2016) which found that diabetes significantly downregulated AQP1 expressions in renal tissues compared with control. Another study also (Nielsen et al, 2002) suggested that the lower aquaporins levels in renal tubules could influence nephron water management and represent the development of acute kidney injury.…”
Section: /16supporting
confidence: 92%
“…STZ animals and control groups were kept in metabolic cages individually and separately and underfeeding and metabolic control. Rats with fasting blood glucose between 200- 250 mg/dl were considered diabetic and included in the experiments for further treatment [14, 15]. Random blood glucose levels were measured daily for 4 successive weeks to assure diabetic incidence.…”
Section: Methodsmentioning
confidence: 99%
“…(USA, Syngene). The band intensity was measured densitometrically using ImageJ Software Version 1.52 (http:/www.imagej.en.softonic.com/) (Ismail et al, 2016).…”
Section: Gene Expression and Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%